The Educational Problems Facing Secondary Stage Students in governmental Schools in the Koura District from the Perspective of Teachers and their Proposals for Treatment - Bani Khalaf, Maisa Mohammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the educational problems facing secondary stage students in governmental schools in the Koura district from the perspective of teachers and their proposals for treatment. To achieve the objectives of the study, the descriptive approach was used through a questionnaire consisted of (25) items, distributed on a classified random sample of (348) male and female teachers. The results of the study showed that the all problems got general average (3.27 to 5) with a moderate estimate, and at the level of domains: the leisure times problems got on the highest average (3.67), with a high estimate, then the instructional problems with an average (3.30), third, the psychological problems with an average of (3.19), Fourth Social Problems with an Average (3.14), and finally the problems related to administration and teachers with an average (3.06), all are appreciated verbal (moderate). The results showed that there were differences in the perspective of teachers about the psychological, instructional and educational problems, and educational problems as a whole, due to the gender variable, in favor of males, there were no differences in the perspective of teachers about all domains of educational problems and educational problems as a whole, due to the variables of educational qualification, and experience. The results indicated that the most prominent proposals for the treatment of educational problems; the proposal "attention to the education of religious conscience" in the first rank, while the proposal "taking care to solve the students’ educational, educational and social problems" in the second rank, and the proposal "providing a safe school environment for students" in the last rank. Based on the results, a set of recommendations and proposals to face the problems of students at the secondary stage.